ANALYSIS Analysis Of Employee Performance Through Work-Life Balance, Workload, And Work Conflict At Nazeera Wedding Organizer: - - Maysa Shafa Afara; I Gede Adiputra (Cita konsultindo, 2024)
Business competition in various industrial sectors in this era of globalization, especially in the creative economy, is very tight. Service provider businesses such as Wedding Organizers (WO) have experienced rapid and significant growth in recent years. This growth creates great opportunities to develop professional businesses that provide planning, organizing, implementing, and evaluating wedding events that are in accordance with the wishes and expectations of clients. To achieve these goals, companies need quality human resources, including skilled and experienced teams and participation from many individuals. This study focuses on the analysis of the influence of work-life balance, workload, and work conflict on employee performance at Nazeera Wedding Organizer. The research sample consisted of 40 employees of the company, using a saturated sampling method. Data were collected through a questionnaire with a Likert scale and analyzed using SmartPLS software version 4 and Structural Equation Modeling (SEM). The results of the study indicate that work-life balance has a positive and significant effect on employee performance, while workload has a positive effect and work conflict has a negative and insignificant effect. Keywords: Work-Life Balance, Workload, Work Conflict, Employee Performance